2007
DOI: 10.1007/s00431-007-0552-6
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection: effect on malnutrition and growth failure in dyspeptic children

Abstract: There are conflicting reports regarding the association of Helicobacter pylori (H. pylori) infection with growth failure. We evaluated the role of H. pylori infection on malnutrition and growth failure in dyspeptic children. The study cases included 108 dyspeptic children and were evaluated by endoscopic gastric biopsy, while 50 healthy children constituted the control group. The study cases were grouped as H. pylori [+] (n = 57) and H. pylori [-] (n = 51) by the presence or absence of microorganism in gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
1
26
0
3
Order By: Relevance
“…In a study evaluating the role of H. pylori infection in malnutrition and growth failure in dyspeptic children, it was found that the nutritional status of H. pylori? and H. pylori-groups were not different; however, the mean daily calorie intake of dyspeptic children who had endoscopically and histologically proven gastritis was lower than that of the control group, independent from the presence of H. pylori [27]. The authors concluded that H. pylori infection is not directly related to malnutrition; however, as a major cause of dyspepsia, H. pylori infection might be considered to cause malnutrition secondary to decreased calorie intake associated with dyspepsia.…”
Section: Discussionmentioning
confidence: 81%
“…In a study evaluating the role of H. pylori infection in malnutrition and growth failure in dyspeptic children, it was found that the nutritional status of H. pylori? and H. pylori-groups were not different; however, the mean daily calorie intake of dyspeptic children who had endoscopically and histologically proven gastritis was lower than that of the control group, independent from the presence of H. pylori [27]. The authors concluded that H. pylori infection is not directly related to malnutrition; however, as a major cause of dyspepsia, H. pylori infection might be considered to cause malnutrition secondary to decreased calorie intake associated with dyspepsia.…”
Section: Discussionmentioning
confidence: 81%
“…The available evidence regarding H. pylori infection and its consequence on growth in pediatric patients is still controversial and different cross-sectional studies that addressed the presence or absence of such association have been reported (34)(35)(36)(37)(38). Such apparent discrepancy and controversial results between various studies may be attributed to the nature and setting of these studies, age, ethnicity and socioeconomic factors of the tested populations, as well as geographical differences and number of H. pylori-infected patients.…”
Section: Discussionmentioning
confidence: 62%
“…H. pylori infection is associated with growth failure and possibly lower ghrelin levels (10). On the other hand, the likelihood of the association between H. pylori and growth failure still remains controversial (11)(12)(13)(14)(15)(16)(17). Some researchers assert that the association of H. pylori infection and growth failure is not a cause-effect relation, but rather, a coincidence of these two entities in low socioeconomic conditions (19).…”
Section: Discussionmentioning
confidence: 97%
“…H. pylori infection leads to a decreased appetite and malabsorption, thus resulting in reduced growth, lowered immunity and repeated infections (11,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation